Dynamics and collapse of local labour markets - Lars Olof Persson (European Regional Science Association (ERSA), 2001)
Sweden has a tripartial regional structure; with a small number of metropolitan regions comparable in size with those on the European Continent, numerous medium sized and small towns, and in addition vast sparsely populated areas. A Parlamentary Commission has recently suggested a regional policy to cope with the uneven economic growth between these regions. The objective should be to maintain and create well performing local labour markets in all parts of the country. The strategy for achieving this is ”regional enlargement, e g extended commuting areas, increased labour mobility and flexibility. The current appr. one hundred local labour market areas range from the majority, which have less than 25 000 inhabitants, to only a few with more than 200 000. Labour mobility options are severely constrained at the small labour markets with only some one hundred industrial branches present, as compared to the dynamic metropolitan regions with five or six times as many. Population projections reveal that the ageing process will reduce the labour force, particularly threatening both the matching processes and the service provision in small and remote regions. It has to be put into question whether this will be solved by traditional labour market mechanisms. In spite of the globalization process, at most local labour markets an increasing proportion of labour demand will be based on community and household basic services. This leads to the question of the spatial consequences of the emerging polarization of the local versus the globally oriented labour market in the service economy. The paper aims at evaluating the economic returns to alternative strategies for “regional enlargement”, labour mobility and flexibility in the different types of regions found in Nordic countries. The specific meaning of polycentric develoment and of urban-rural partnership in the Nordic context will be discussed. By analysing individual labour market careers recorded in annual gross stream statistics, multidimensional mobility options are calculated and projected for a range of local labour market areas. Methods in spatial planning for evaluating labour market performance are suggested.
Keywords: 330